Photoreceptor cross-talk in UV-B photomorphogenesis in tomato (Solanum lycopersicum) : screening through phytochrome and cryptochrome mutants : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Plant Biology at Massey University, Palmerston North, New Zealand - Pabellon, Ivie V S (Massey University, 2017)
Plant photoreceptors detect changes in the light environment and induce differential gene expression, resulting in the appropriate physiological and morphological responses. Under full sunlight, phytochromes, cryptochromes and the UV-B photoreceptor, UVR8 (UV-B RESISTANCE LOCUS 8), destabilize PHYTOCHROME INTERACTING FACTORS (PIFs) to inhibit elongation. PIFs are transcriptions factors that inhibit light-regulated genes, including auxin-related genes involved in cell elongation. In the shaded environment, the reduction in the spectral composition detected by the photoreceptors results in the activation of elongation and PIF activity. However, recent studies have shown that low levels of UV-B can still inhibit the elongation under shade. Most photobiology studies that investigated plant responses to shade have concentrated on the model species, Arabidopsis thaliana. In contrast, Solanum lycopersicum (tomato) is another model system, but few studies have investigated plant responses to shade in tomato due to its sympodial architecture and presence of internodes which A. thaliana lacks. In this study, phytochrome and cryptochrome tomato mutants were exposed to low levels of UV-B under photosynthetically active radiation (PAR) as background light to investigate the possible crosstalk between these photoreceptors and the UV-B photoreceptor of tomato in regulating hypocotyl or internode elongation. Out of all the multiple phytochrome and one cryptochrome mutants, phyAphyB2 mutant exhibited an impaired UV-B inhibition of internode elongation after three days of UV-B treatment. End-point PCR on the gene expression of PIF4 together with two UV-B responsive genes and genes involved in the catabolism of active gibberellin could not explain the impaired response of phyAphyB2. Nevertheless, physiological measurements indicate that phyA and phyB2 of tomato may be acting redundantly in mediating the UV-B induced inhibition of internode.
Figures 1.1, 1.3, 1.4 and 1.5 removed for copyright reasons
Keywords: Tomatoes; Photomorphogenesis; Photoreceptors; Research Subject Categories::NATURAL SCIENCES::Biology::Organism biology::Plant physiology